2020
DOI: 10.3390/info11040215
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Sustainable Technology in the Malaysian SMEs Sector: Does the Role of Government Matter?

Abstract: This paper looks at the role of government as a novel dimension in the adoption of sustainable technology by small and medium enterprises (SME) in Malaysia. This determinant stems from the fact that, in many transitional economies, private sector organizations encounter resource constraints as a barrier to innovation adoption. This is especially the case with sustainable technology incorporated into business operations. Therefore, third party intervention into the adoption process becomes inevitable and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 61 publications
0
21
0
2
Order By: Relevance
“…Externally, persuasion based on credibility, sympathy, and logic will refine and impose arguments on people's attitudes, affecting their moral duty ( 42 ). In addition to the antecedents, external influences such as eco-centrism and altruism are thought to impact attitudes ( 43 ). Those working on sustainability studies have a diverse range of views on technology.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Externally, persuasion based on credibility, sympathy, and logic will refine and impose arguments on people's attitudes, affecting their moral duty ( 42 ). In addition to the antecedents, external influences such as eco-centrism and altruism are thought to impact attitudes ( 43 ). Those working on sustainability studies have a diverse range of views on technology.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, it has been observed that tariffs are the most efficient and profitable mechanism for encouraging sustainable technologies, rather than other instruments, like quotas, direct incentives, or voluntary goals [66]. However, government subsidies or incentives do not have to be only financial.…”
Section: Sustainability and Interventionmentioning
confidence: 99%
“…Innovative, non-monetary incentives, like providing public recognition or awards, can be as efficient as financial subsidies over the long-term [67]. It is important to mention that government support might have many purposes, including educating organizations about the use of sustainable technology, changing companies' behavior towards sustainability, and establishing a more environmentally friendly relationship [66].…”
Section: Sustainability and Interventionmentioning
confidence: 99%
See 2 more Smart Citations